The Influence of Corporate Social Responsibility and Firm Size on Firm Value with Audit Committee as Moderating Variable - Inaya Wulandari; Muhammad Nur Rizqi; Verni Asvariwangi (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2026)
Corporate Social Responsibility (CSR) and firm size on firm value with the audit committee as a moderating variable were examined in energy sector companies listed on the Indonesia Stock Exchange. This study employed a quantitative approach using panel data analysis processed through EViews. Data were collected through purposive sampling, resulting in 30 companies and 120 observations, of which 20 outlier data were excluded, resulting in 100 final observations. The data were analyzed using panel data regression and Moderated Regression Analysis (MRA). The findings indicate that CSR has a negative and significant effect on firm value, while firm size does not significantly affect firm value. Furthermore, the audit committee moderates the relationship between CSR and firm value, but does not moderate the relationship between firm size and firm value. These findings indicate that the audit committee plays an important role in strengthening CSR implementation to enhance firm value